The Influence of Principal Leadership, Work Motivation and Organizational Culture on Teacher Performance - Norpa Mailani; Lantip Diat Prasojo (STKIP Singkawang, 2025)
Teachers and school principals are the most crucial participants in the implementation of teacher education. In addition to their roles and responsibilities, teachers as a profession are at the center of every attempt to improve the quality of education via educational reform. The purpose of this study is to determine the extent to which organizational culture, work motivation, and principal leadership affect the performance of State Vocational School teachers in Indragiri Hilir Regency. This study focuses on issues that affect the performance of these teachers. Ex post facto research, or after the fact, is the methodology used in this study. Data was gathered at State Vocational High Schools in Indragiri Hilir Regency via questionnaires. Instruments created by the researcher himself were used to gather data from each research variable. Using the IBM SPSS software, data analysis employs both a multiple regression test and a basic linear regression test. With a significance of 0.000 <0.05, an Fcal value of 39.928 greater than the Ftabel of 3.05, and a Coefficient R Square of 0.422, the study's findings indicated that the principal's leadership, work motivation, and organizational culture had a positive and significant impact on teachers' performance at State Vocational Schools in Indragiri Hilir Regency. This indicates that 42.2% of teacher performance is influenced by corporate culture. All pertinent parties actively participate in initiatives aimed at enhancing teacher performance, such as hiring competent teaching candidates.